339 Human biomonitoring for exposure assessment of benzene during short-term maintenance work. (24th April 2018) - Jäger, T; Bäcker, S; Oberlinner, C; Bader, M
Abstract : Introduction: Human biomonitoring (HBM) is frequently used for exposure analysis and assessment of maintenance workers potentially exposed to benzene during turnaround works. In Germany, the Technical Rule for Hazardous Substances (TRGS) 910 provides three biomarkers for benzene: S-phenylmercapturic acid (SPMA), trans, trans-muconic acid (ttMA) and unmetabolized benzene in urine. The aim of the present HBM study was to compare the validity and applicability of the different biomarkers for exposure assessment during a turnaround. Methods: In 2016, 143 post-shift urine samples of 119 maintenance workers with potential exposure to benzene were analysed. In each sample urinary benzene, SPMA and ttMA were measured according to procedures recommended by the German Research Foundation (DFG). The biomonitoring equivalents of the tolerance concentration according to the TRGS 910 were used as internal action values: 0.5 mg ttMA/g creatinine, 25 µg SPMA/g creatinine, 5 µg benzene/L urine. Results: The median values were 0.09 mg/g creatinine (range:<LOQ – 1.76 mg/g creatinine) for ttMA, <LOQ (range:<LOQ – 73.5 µg/g creatinine) for SPMA and 0.5 µg/L (range: 0.1–9.9 µg/L) for urinary benzene. Action value excursions were observed in less than 2% of the post-shift samples for SPMA, 4% for ttMA and 7% for urinary benzene, respectively. However, the results showed that the action value excursions were not necessarily observed in the same samples, probably resulting from, e.g., peak exposures and different elimination half-lives. Conclusion: The HBM program has shown a low overall occupational exposure to benzene during turnaround works. With respect to applicability and validity, urinary SPMA is the biomarker of choice for the reliable HBM of benzene exposures. ttMA has a critically low diagnostic sensitivity, while unmetabolized urinary benzene demands special attention to avoid external contamination. Nevertheless, urinary benzene allows for a rapid and relatively cost-efficient analysis and it is well suitable for screening purposes.